2010
DOI: 10.1111/j.1365-2265.2010.03845.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone supplementation on markers of the metabolic syndrome and inflammation in hypogonadal men with the metabolic syndrome: the double‐blinded placebo‐controlled Moscow study

Abstract: SummaryObjective Men with the metabolic syndrome (MetS) have low plasma testosterone (T) levels. The aim of this study was to establish whether the normalization of plasma T improves the features of the MetS. Design A randomized, placebo-controlled, double-blinded, phase III trial of 184 men suffering from both the MetS and hypogonadism. Patients One hundred and eighty-four men, aged 35-70, with the MetS and hypogonadism (baseline total T level <12AE0 nm or calculated free T level <225 pm.), recruited in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
271
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(297 citation statements)
references
References 70 publications
16
271
5
3
Order By: Relevance
“…Previous RCTs of testosterone therapy in men with diabetes or the metabolic syndrome, summarized in Supplementary Table 1, yielded inconsistent outcomes (20,(35)(36)(37). The largest RCT, although unpublished, in 180 men with T2D did not report any significant changes in HOMA-IR or HbA 1c (accessed at http:// www.solvaypharmaceuticals.com/static/ wma/pdf/1/3/4/4/2/S176.2.101.pdf).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous RCTs of testosterone therapy in men with diabetes or the metabolic syndrome, summarized in Supplementary Table 1, yielded inconsistent outcomes (20,(35)(36)(37). The largest RCT, although unpublished, in 180 men with T2D did not report any significant changes in HOMA-IR or HbA 1c (accessed at http:// www.solvaypharmaceuticals.com/static/ wma/pdf/1/3/4/4/2/S176.2.101.pdf).…”
Section: Discussionmentioning
confidence: 99%
“…Dropout rates were 29% at 6 months and 46% at 12 months (37). A 30-week RCT of testosterone therapy conducted in 184 men with the metabolic syndrome, 56 of whom had T2D, showed a 31% improvement in HOMA-IR with testosterone treatment, in association with significant weight loss (24.3 kg), although changes in body composition were not assessed (36). The findings in these RCTs are consistent with the possibility that testosterone treatment may have more favorable effects on glucose metabolism in men without established diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…84 A randomized, placebo-controlled, doubleblind trial of 184 men with hypogonadism and metabolic syndrome showed that intramuscular administration of testosterone undecanoate decreased plasma levels of interleukin-1b, tumor necrosis factor-a and C-reactive protein in association with reductions in body mass index and waist circumference, while interleukin-6 and interleukin-10 did not change significantly. 85 Taken together, testosterone administration, at least in hypogonadal men, may have a favorable vascular effect, including endotheliumdependent or -independent vasodilation and reduction of arterial stiffness and inflammatory markers. In contrast, the effects of testosterone replacement on the progression of carotid intima-media thickness or other atherosclerotic lesions, as well as on CVD risk, 86 are unknown.…”
Section: Clinical Effects Of Androgen Replacement Therapymentioning
confidence: 99%
“…Six RCTs have been conducted to date specifically in men with diabetes or the metabolic syndrome (Kapoor et al 2006, Gopal et al 2010, Kalinchenko et al 2010, Jones et al 2011; Tables 1 and 2). One was never unpublished (http://www.solvaypharmaceuticals.com/ static/wma/pdf/1/3/4/4/2/S176.2.101.pdf) and one has been presented in preliminary abstract form (Hackett et al 2013).…”
Section: Testosterone Treatment In Men With Metabolic Disordersmentioning
confidence: 99%